2017
DOI: 10.1002/chir.22741
|View full text |Cite
|
Sign up to set email alerts
|

Absolute configuration of the ocimene monoterpenoids from Artemisia absinthium

Abstract: The absolute configuration (AC) of the naturally occurring ocimenes (-)-(3S,5Z)-2,6-dimethyl-2,3-epoxyocta-5,7-diene (1) and (-)-(3S,5Z)-2,6-dimethylocta-5,7-dien-2,3-diol (2), isolated from the essential oils of domesticated specimens of Artemisia absinthium, followed by vibrational circular dichroism (VCD) studies of 1, as well as from the acetonide 3 and the monoacetate 4, both derived from 2, since secondary alcohols are not the best functional groups to be present during VCD studies in solution due to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…A complementary structure confirmation for 3 was gained after PERCH 10 simulation of the complete 1 H NMR spin-spin system, as was recently reported for monoterpenes derived from ocimene 11 and for cholesterol. 12 The data revealed that the 1.2 Hz coupling constant is due to a 4 J 1,12a interaction, which is not directly evident by inspection of the spectrum since H-12a appears as a broadened doublet 3 J 6a,12a = 3.8 Hz, as H-12a also produces a long-range couplet with H-6A.…”
supporting
confidence: 57%
“…A complementary structure confirmation for 3 was gained after PERCH 10 simulation of the complete 1 H NMR spin-spin system, as was recently reported for monoterpenes derived from ocimene 11 and for cholesterol. 12 The data revealed that the 1.2 Hz coupling constant is due to a 4 J 1,12a interaction, which is not directly evident by inspection of the spectrum since H-12a appears as a broadened doublet 3 J 6a,12a = 3.8 Hz, as H-12a also produces a long-range couplet with H-6A.…”
supporting
confidence: 57%
“…The VCD spectra compared well with the calculated spectra of the 2 enantiomers. 31 VCD studies of 2 isolates 32 from Bubonium graveolens provided their AC as (−)-(1S,5R,6S)-2,7,7-trimethylbicyclo[3.1.1] hept-2-en-6-yl acetate (19) and its acetyl derivative 20 (Figure 4). The compounds were already known in the species, although this is the first report on the AC of (−)-20.…”
Section: Monoterpenoids the Formulas Of The 28 Monoterpenoids Includmentioning
confidence: 99%
“…A general lack of VCD studies of acyclic monoterpenes like linalol, citronellol, and citronellal is observed, although the ocimenes from the essential oils of Artemisia absintium could be studied [24] since a significant molecular portion is rigid due to the presence of a conjugated diene. Of relevance is also to note that an AC study of conformational very flexible citronellal by molecular rotational resonance, using microwaves in the 2-8 GHz region, was reported recently [25], also evidencing a very high number of relevant conformers.…”
mentioning
confidence: 99%